1989
DOI: 10.1111/j.1559-1816.1989.tb01459.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat and Violence in the Dallas Field Data: Linearity, Curvilinearity, and Heteroscedasticity1

Abstract: Harries and Stadler (1988) observed only a positive linear trend, with no curvilinear relationship, between heat and violence in their 1980–81 Dallas field data. When Cotton (1986) observed similar trends in his data, we noted that in fact the variance in violence increases with temperature (Bell & Fusco, 1986). We report here similar statistically significant heteroscedasticity in the Harries and Stadler data. We propose that both aggressive and escape tendencies increase with high ambient temperatures, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 9 publications
0
16
1
Order By: Relevance
“…Due to an absence of air conditioning on inmate housing units, hot temperatures could be related to aggressive incidents. Studies done outside the prison environment have indicated a possible linear relationship between heat and assaultive behavior (Cotton, 1986;Harries & Stadler, 1983, 1988 some evidence suggests that if there is a relationship, it may be curvilinear (Bell & Fusco, 1989).…”
Section: Situational Studiesmentioning
confidence: 99%
“…Due to an absence of air conditioning on inmate housing units, hot temperatures could be related to aggressive incidents. Studies done outside the prison environment have indicated a possible linear relationship between heat and assaultive behavior (Cotton, 1986;Harries & Stadler, 1983, 1988 some evidence suggests that if there is a relationship, it may be curvilinear (Bell & Fusco, 1989).…”
Section: Situational Studiesmentioning
confidence: 99%
“…Finally, some implications of the results are discussed. The temperature-aggression relationship has been examined both in field studies and laboratory studies (Baron, 1972(Baron, , 1976Baron and Bell, 1975, 1976;Bell and Baron, 1976;Baron and Ransberger, 1978;Anderson and Anderson, 1984;Cotton, 1986;Kenrick and MacFarlane, 1986;Anderson, 1987;Rule, Taylor, and Dobbs, 1987;Harries and Stadler, 1988;Bell and Fusco, 1989). In particular, the field studies show a consistent pattern: uncomfortable heat (25 degrees to 30 degrees Celsius) increases aggression (see Anderson (1989) for a review of this literature).'…”
mentioning
confidence: 91%
“…Some previous studies have found evidence of a reduction in assaults with very high temperatures, with an inflection point of around 90°F (32.2°C; Bell and Fusco 1989;Cohn and Rotton 2005; Gamble and Hess 2012). We did not find evidence of such a non-monotonic relationship, although temperatures in New Zealand do not generally reach levels high enough to test this proposition (the highest daily mean temperature observed in the study data was 27.7°C).…”
Section: The Relationship Between Temperature and Assault: Form And Mmentioning
confidence: 94%
“…The general affective aggression model (Anderson et al 1995) suggests that uncomfortable temperatures can increase aggressive cognitions and emotions and thereby increase the incidence of aggressive behaviour. Similarly, the negative affect escape model (Bell and Baron 1976; see also Bell and Fusco 1989) suggests that unpleasant situational variables such as uncomfortable temperatures can increase negative affect, and that negative affect increases aggressive behaviour. However, in the negative affect escape model this relationship is hypothesised to hold only up to an (unspecified) inflection point, beyond which extremely high levels of negative affect prompt escape from the situation.…”
Section: The Mechanism Of the Temperature-violence Relationshipmentioning
confidence: 95%
See 1 more Smart Citation